Hybrid membrane of flat silk cocoon and carboxymethyl chitosan formed through hot pressing promotes wound healing and repair in a rat model - Wu, Baiqing; Tong, Xiaoling; Cheng, Lan; Jiang, Sha; Li, Zhi; Li, Zheng; Song, Jiangbo; Dai, Fangyin (Frontiers in Bioengineering and Biotechnology, 2022)
Clinical wound management is always a relatively urgent problem，Besides, the wounds, especially severe wounds with excessive tension or inability to keep quiet, are prone to tissue infection, necrosis and other undesirable phenomena in the healing process. Therefore, a low-cost complementary treatment has always been a topic of many researchers, It is very urgent to innovate a low-cost dressing that can adapt to the high mechanical requirements and complex wound conditions . At present, the construction of artificial skin with structure similar to normal skin through tissue engineering is an effective means to solve this kind of regeneration and repair problems of serious wound. In this study, the flat silk cocoons (FSC) was hot pressed with carboxymethyl chitosan (CMCS) to generate cross-linking binding without enzyme or cross-linking agent, so as to simulate the 3 D structural composites of the skin cuticular layer, showing large potential to reduce the inflammatory cells and promote the neovascularization in the process of skin wound repair. After hot pressing at 130°C and 20 Mpa, the FSC/CMCS composite material was denser than FSC in structure. Meanwhile, it was strong in light transmission and could be arbitrarily cut. Simulating the normal skin tissue structure, it overcame the poor mechanical properties of traditional support materials. Besides, the combination of protein and polysaccharide simulated the extracellular matrix in composition, so the material was of better biocompatibility. The results have shown that the FSC/CMCS composite support material has excellent mechanical properties and it can provide a low-cost and environment-friendly process for making dressings. In addition, this paper preliminarily reveals the mechanism of scaffolds promoting the healing of full-thickness skin defects on the back of SD rats. In vivo experiments using a full-thickness skin defect model indicated that FSC/CMCS membranes significantly promoted the rate of wound healing, Exhibiting good for blood vessel formation and less inflammatory reaction. This bionic support structure, with excellent repair efficacy on the deep skin defect wound, has further improved the biomaterial system, such as skin and other soft tissues.